Forecasting Product Demand at PT. Sinar Sosro Kp Cimareme West Bandung - Jaja, Jaja; Nurendang, Nadia; Nurfauzia, Fadila (SINTESA, 2024)
Companies need a method, namely forecasting (Kurniadi, 2018). Forecasting (forecasting) is the most important part for every company or business organization in every management decision making. Apart from that, forecasting is usually done to reduce uncertainty about something that will happen in the future (Vanesa, et al. 2018). PT. Sinar Sosro KP Cimareme West Bandung forecasts demand using sales patterns according to targets determined by the company. The choice of demand forecasting method uses quantitative methods with moving average forecasting which shows that past data can be used as a guide for forecasting in the future. the moving average model is a forecasting model used by researchers in research at PT. Sinar Sosro KP Cimareme West Bandung as a forecasting model uses time series data which is in accordance with the data provided by the company. The results of demand forecasting using the moving average model for 3 months produced a unit value of 350ml, TBE products of 13,546 crates, 4,869 TBE 450ml products, 1,453 crates of TBE LS 450 KL12 products, 1,563 crates of TBE GT 450 K12 products. crates, 23,483 crates of 350ml FTE products, 11,302 crates of 500ml FTE products, 5,725 crates of 350 K12 STE products, 1,673 crates of 500ml STE products, 1,554 crates of 500ml TSE products, 61 crates of 310ml FTC products, 536 crates of 330ml TSC products crate , and finally the 230ml FTO product is 333 crates of OWP PETCompanies should be able to pay attention to controlling demand for OWP PET products in 12 product units, to avoid errors in demand and avoid lost stock and over stock in each product unit, and control is carried out to avoid damaged products, namely products that are expired or have leaks. It would be better for the company to be better able to organize or coordinate each product that will be sent to outlets in the West Bandung Region so that the company can ensure the accuracy of forecasting demand for OWP PET products.